Do Start-ups Provide Employment Opportunities for Disadvantaged Workers? - Fackler, Daniel; Fuchs, Michaela; Hölscher, Lisa; Schnabel, Claus (Industrial & Labor Relations Review, 2019)
This article compares the hiring patterns of start-ups and incumbent firms to analyze whether start-ups offer relatively more job opportunities to disadvantaged workers. Using administrative linked employer–employee data for Germany that provide the complete employment biographies of newly hired workers, the authors show that young firms are more likely than incumbents to hire applicants who are older, foreign, or unemployed, or who have unstable employment histories, arrive from outside the labor force, or were affected by a plant closure. Analysis of entry wages shows that penalties for these disadvantaged workers, however, are higher in start-ups than in incumbent firms. Therefore, even if start-ups provide employment opportunities for certain groups of disadvantaged workers, the quality of these jobs in terms of initial remuneration appears to be low.
CRIS-Team Scopus Importer:2019-09-20
Keywords: employment; linked employer–employee data; start-ups; wages; young firms; Diversity